Management of Dystocia in Buffalo by Partial Percutaneous Fetotomy: A Case Report - Nistane, Saurabh; Muthuswamy J, Aadhithya; Pachaiyappan M; Vadera, Vishnu; Solanki, Manish; Srivastava, Neeraj; Kumar, Brijesh; Khan, MH (Animal Reproduction Update, 2025)
A five-year-old, nondescript buffalo in her third parity, with a history of 9 months of gestation, in labour pain since 12h, was presented at the Referral Veterinary Polyclinic, ICAR-Indian Veterinary Research Institute, Izatnagar, Bareilly, with no further progression and a ruptured water bag. It was previously attended by a paravet in the morning with faulty manual traction, causing the forelimbs to track outside the vulva up to the fetlock joint with no further progression. Clinical examination revealed an increase in respiration and pulse rate with rectal temperature 102.6ºF was recorded. On per rectal and per vaginal examination, there was complete dilation of the cervix, the foetal presentation was anterior longitudinal dorso-sacral position, and the head and neck were extremely downward deviated in terms of posture, while the forelimbs were outside the vulva up to the fetlock joint. Successful management of dystocia with partial percutaneous fetotomy and mutational operation was performed with uneventful recovery of the animal.